WHEN AFFECTION IS SILENT: MOURNING FOR ABANDONMENT IN THE LIFE OF THE ELDERLY WOMAN - Ramos, Semirames Cartonilho de Souza; Costa, Cintia Bezerra Almeida; Moreira, Giulia Serrano; Soares, Laura Catarina Siqueira; de Oliveira, Virgínia Soares; Junior, Orácio Carvalho Ribeiro; Filho, Esdras Ramos Cartonilho; França, Jael Rúbia Figueiredo de Sá; Pereira , Maria Suely de Souza; Trajano, Ana Luiza Dias; Silva, Giovanna Stélling Brito de Araújo; Carneiro, Ana Lúcia Basilio (Seven Editora, 2024)
Aging is a natural phenomenon, initiated from birth, evidenced by functional, physical and psychological changes that become noticeable in old age. In the female dimension, menopause can be characterized as the initial milestone of the aforementioned process, and aging is commonly marked by situations of affective abandonment, absence of emotional support and emergence of emotional reactions such as grief, a scenario explored in this chapter. The objective is to categorize and explore the physical, emotional and social manifestations of affective abandonment and grief in elderly women. The methodology adopted for this work is based on a narrative review of the literature, with the objective of exploring the dynamics of affective abandonment and grief in the health of elderly women. Searches were carried out in scientific databases such as PubMed, Scielo, LILACS and gray literature Google Scholar, using the descriptors "elderly women's health", "affective abandonment", "mourning" and their English correspondents, according to the DeCS/MeSH criteria. Among the main results, it can be highlighted that grief triggers implications in the physical, emotional and social spheres, and the State should devise and execute public policies concerning the theme. It is concluded that the health of elderly women requires multidisciplinary attention and action, especially with regard to the scenarios in which affective abandonment and grief are present, given that such phenomena alter and intensely affect the quality of life of the population.DOI: https://doi.org/10.56238/sevened2024.037-094